Positioning: How to Be Seen and Known - Mitrakasem, Orajanya (Journal of Architectural/Planning Research and Studies (JARS), 2002)
In today’s business, political, and academic situations, people often misunderstand the role of communication. There are many forms of media and advertising. We, architects, architectural companies, or schools of architecture, need to think about how to be seen and known in an over-communicated society and marketplace. We need to create a “position” in the prospect’s mind to grip with the problems of communicating. “Positioning” is all about understanding the psychology of the mind and how we can manipulate perceptions to make whatever we are selling more attractive and unique. It is how we differentiate our product in the minds of our customers and prospects. It is not too hard to get into the mind. The answer is to be the first. If we cannot be the first, we need to find a way to cope with the product or the person who did get there first. Then, we must find the way to maintain leadership by searching for what we do not need and what we do need to do. Also, there are many strategies for staying on the top such as covering all bets, understanding the power of product, establishing multibrands, etc. Nevertheless, the truth is that if we cannot get to the top rung, we should have to admit and we subsequently have to let it go. Then, if we cannot be a leader, how can we position ourselves as a follower. It’s different between being a leader and being a follower. There are many ways to find specific positions not being occupied by anyone else such as size, price strategies, or technology. Finally, how can we play the positioning game; it needs to be carefully justified. To be successful at positioning, we must have the right mental attitude. We need to become an outside-in thinker rather than an inside-out thinker, which requires patience, courage, and strength of character.